2022
DOI: 10.2174/1570162x20666220428103250
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Free Amino Acid Profile in HIV-Positive Cases

Abstract: Background: Increasing the sensitivity and availability of LC-MS / MS devices may provide advantages in terms of revealing the changes in metabolic pathways in HIV-positive patients and elucidating the physiopathology. Introduction: The aim of this study was to determine the difference in amino acid level between HIV-positive patients and healthy individuals by using LC-MS / MS, and to investigate its relationship with HIV infection. Material and Methods: Concentrations of 36 different amino acids and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Moreover, research suggests that HIV infection directly or indirectly induces dopamine dysfunction ( 35 ), a finding also supported by our results. Some studies have reported significantly lower levels of linoleic acid and argininosuccinic acid in individuals with HIV-1 ( 36 , 37 ), and an increase in brain choline compounds before the onset of AIDS dementia in PLWH ( 38 ). Furthermore, palmitic acid has been studied for its ability to inhibit HIV-1 infection by blocking effective attachment between gp120 and CD4 ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research suggests that HIV infection directly or indirectly induces dopamine dysfunction ( 35 ), a finding also supported by our results. Some studies have reported significantly lower levels of linoleic acid and argininosuccinic acid in individuals with HIV-1 ( 36 , 37 ), and an increase in brain choline compounds before the onset of AIDS dementia in PLWH ( 38 ). Furthermore, palmitic acid has been studied for its ability to inhibit HIV-1 infection by blocking effective attachment between gp120 and CD4 ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study provided a robust and rapid approach to characterizing inflammation and immune-related amino acid metabolites, which can be prospectively used in biomarker discovery to assess inflammation and immunity states in various pathological conditions. Still, another research work provided a comparison of serum amino acid metabolites in healthy control and HIV-infected subjects [ 144 ]. These authors utilized a targeting method based on LC-MS/MS, which helped rapidly characterize immune changes and inflammation-related metabolites.…”
Section: Research Field Landscapementioning
confidence: 99%